PANDUAN PROSES PENYUSUNAN LAPORAN KEBERLANJUTAN (STUDI KASUS UMKM ARDUNG FARM) - Elsa Nur Maulidina Praptika Ayu (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the modeling of the Sustainability Report Preparation Process at Ardung Farm MSMEs based on the formulation of the problem and research objectives. In addition, to improve the efficiency and effectiveness of the sustainability report preparation process. This research method uses a descriptive qualitative approach that emphasizes understanding the meaning and process rather than just the results of an activity. Information obtained through certain measurements is used as a basis for compiling logical arguments into facts. Based on the results of the study, the owner of Ardung Farm MSMEs considers sustainability reports important as a tool for evaluating and improving long-term businesses that have a positive impact on the environment and society. Employees also consider this report to support welfare and environmental impact management, although their involvement in sustainability is still limited. Suppliers support the preparation of reports as a form of social responsibility and sustainable innovation, while the community expects this MSME to continue to monitor its operational impacts, especially if the business scale increases. MSME partners consider chicken waste management to be good, but formal reports are needed to expand partnerships and their positive impacts.